Students’ Speaking Ability Using Cartoon Movie During Pandemic COVID-19 - Darto (PGRI Provinsi Jawa Timur, 2022)
This research was aimed to describe the student’s improvements and their responses toward the use of cartoon movie in speaking skill of expression of giving and responding instruction by the ninth graders in SMPN 55 Surabaya during Pandemic COVID-19 academic year 2020/2021. In order to conduct research, the classroom action research (CAR) was used on 36 students in IX B class as subjects. Observation and tests were the instruments used. The results showed in the preliminary results showed that there were 1 or 3% of 38 students got poor mark, 8 or 21 % of 38 students got less mark, 16 or 42% of 38 students got fair mark, and 13 or 34% of 38 students got good mark. Then, in cycle 1, 2 or 5.2% of 38 students got excellent mark, 32 or 84.3% students of 38 students got good mark, and 4 or 10.5% of 38 students got fair mark. The results of cycle 2 revealed that 21 or 55.3% of 38 students got excellent mark, 17 or 44.7% students of 38 students got good mark. The researcher’s analysis shows that the average of student’s test result of the second cycle was 82.84. The highest score was 92 and the lowest score was 68. Researcher concluded that student’s speaking skill in expression of giving and responding instruction was improved and effective.